Exploring Factors and Impact of Blockchain Technology Adoption in the Food Supply Chains - Mohammed, Abubakar (Curtin University, 2023)
Globalization has also increased the complexity and difficulty of addressing these issues and enhancing efficiency in FSCs. The adoption of blockchain technology (BCT) has been proven to have the potential to transform the FSC based on its potential benefits. BCT promises to improve FSC processes. However, little is known about the factors that drive blockchain adoption within the FSC and the impact of BCT supply chain processes, as empirical evidence is scarce within the existing literature. This study, therefore, explores key factors, impacts, and challenges of blockchain adoption in the FSC.